Economic challenges ahead for the next European Commission - Clemens Fuest (CESifo GmbH, 2024)
The past few years have been marked by major crises, including the covid pandemic and the Russian attack on Ukraine. These crises have consequences. The new European Commission will need a well thought-out economic policy agenda to respond to the changed geopolitical challenges and to strengthen its competitiveness. This policy brief analyzes the main economic challenges faced by the EU: improving defense capabilities, overcoming international frictions, and refining its environmental and climate change policies.
Keywords: 330